The Dog Listener - Fennell, Jan. (London : HarperCollins, 2000)
Janet Fennell's understanding of the canine world and its language has enabled her to bring even the most desperate and delinquent of dogs to heal. This guide to Fennell's techniques draws on her countless case histories of training problem dogs.
Includes index.
Keywords: Dogs -- Training; Dogs -- Psychology; Pets